Snagfall the first decade after severe bark beetle infestation of high‐elevation forests in Colorado, USA. Issue 3 (21st January 2020) - Rhoades, Charles C.; Hubbard, Robert M.; Hood, Paul R.; Starr, Banning J.; Tinker, Daniel B.; Elder, Kelly
Abstract: The persistence and fall rate of snags (standing dead trees) generated during bark beetle outbreaks have consequences for the behavior, effects, and suppression of potential wildfires, hazard tree and timber salvage operations, wildlife habitat, and numerous ecosystem processes. However, post‐beetle snagfall dynamics are poorly understood in most forest types. We tagged standing live and dead lodgepole pine ( Pinus contorta ), subalpine fir ( Abies lasiocarpa ), and Engelmann spruce ( Picea engelmannii ), including beetle‐killed pine snags following the peak of a recent mountain pine bark beetle outbreak in watersheds at the Fraser Experimental Forest in northcentral Colorado and sampled snagfall 10 and 12 years later. Bark beetle attacks began in 2003, peaked by 2006, and killed 78% of overstory lodgepole pine in 133 plots distributed across a range of stand and site conditions. Of those snags, only 17% fell between 2007 and 2018. Most snags broke at ground level, due to butt rot, and were oriented downhill. In contrast, snags that tipped up or snapped off above the ground were oriented with the prevailing winds. Equal numbers of snags fell singly and in multiple‐tree groups, and equal numbers remained elevated rather than in contact with the ground. Lodgepole pine snagfall was 1.6‐times higher on steep slopes (>40%) where dead pine density was higher, compared to flatter sites. Based on our findings and previous research, we estimate that one‐half the beetle‐killed lodgepole pine in high‐elevation forests such as those at Fraser may fall within 15–20 yr of beetle infestation, but that some pine snags are likely to persist for decades longer. Post‐outbreak snagfall dynamics create a multiple‐decade legacy of bark beetle outbreaks that will persist longer in high‐elevation compared to lower‐elevation forests.